In silico investigation and assessment of plausible novel tyrosinase inhibitory peptides from sesame seeds. (July 2021) - Baskaran, Roshni; Chauhan, Shweta Singh; Parthasarathi, Ramakrishnan; Mogili, Nirupa Shyam
Abstract: Tyrosinase, the copper containing enzyme is responsible for undesirable browning in various fungi, fruits and vegetables during their post-harvest storage and processing. Currently available tyrosinase inhibitors have limitations leading to their restricted applications in the food sector. There is an indispensable need for unravelling new, natural, efficient and non-toxic inhibitors to address enzymatic browning. This study, hence focussed on the identification of bioactive peptides from sesame seed proteins for inhibition of tyrosinase activity using in silico methodologies. Proteins, 11S Globulin and 2S Albumin were chosen for proteolytic digestion using the BIOPEP tool. Eight peptides, namely AH, ECA, EL, IR, LK, RHF, VY and WDR with antioxidant potential were obtained. Based on molecular docking analysis, the peptide inhibitors were found to have higher binding affinities to mushroom tyrosinase in comparison to kojic acid and inhibited the enzyme by chelating the copper ions at the active site. The peptides IR, LK and VY were found to be the most effective inhibitors and were non-toxic as well as non-carcinogenic according to toxicity analysis. The findings of this study indicate that the small peptides obtained from sesame seeds hold promise as novel and safe tyrosinase inhibitors to mitigate post-harvest losses in the food industry. Highlights: Browning of foods is an important cause for post-harvest losses in the food industry. Tyrosinase enzyme is responsible for the enzymatic browning of foods. In silico methods were used to predict tyrosinase inhibitory peptides from sesame seed proteins. Sesame based peptides inhibited tyrosinase enzyme by chelating copper ions at the active site. Sesame based peptides offer promise for the development of effective and safe tyrosinase inhibitors.